Region-Specific Objective Signatures of Endoscopic Surgical Instrument Motion: A Cadaveric Exploratory Analysis - Harbison, R. Alex; Berens, Angelique M.; Li, Yangming; Bly, Randall A.; Hannaford, Blake; Moe, Kris S. (Journal of Neurological Surgery Part B: Skull Base, 2017)
Objectives The objective of this study was to evaluate region-specific surgical instrument kinematics among novice and experienced surgeons performing endoscopic endonasal skull base surgery.Design Cadaveric experimental study.Setting Tertiary academic center.Participants Two novice and two experienced surgeons performed eight endoscopic total ethmoidectomies and sphenoidotomies using an optically tracked microdebrider.Main Outcome Measures Time-stamped Euclidian coordinates were recorded. Cumulative instrument travel, mean linear velocity and acceleration, and mean angular velocities were calculated in the anterior ethmoid, posterior ethmoid, and sphenoid sinus regions.Results Mean cumulative instrument travel (standard deviation) was highest in the posterior ethmoid region for both novice and experienced surgeons (9,795 mm [1,664] vs. 3,833 mm [1,080]). There was a trend in mean linear and angular velocities, and acceleration with increasing magnitudes for experienced surgeons compared with novices. Among experienced surgeons, we observed a trend of decreasing yaw velocity during the approach to the surgical target.Conclusions We present a novel method of evaluating surgical instrument motion with respect to anatomical regions of the skull base during endoscopic endonasal skull base surgery. These data may be used in the development of surgical monitoring and training systems to optimize patient safety.
Keywords: surgical instrument motion; kinematics; skull base; surgical safety; surgical training